1999
DOI: 10.1016/s0022-5223(99)70259-x
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular discordance: Results of repair in 127 patients

Abstract: Analysis of conventional management of atrioventricular discordance revealed cumulative increases in mortality, systemic atrioventricular valve (tricuspid) replacement, complete atrioventricular block, and incidence of reoperation. Alternative management should be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…As in our patient group, it is implemented to treat conduit stenosis by percutaneous intervention in patients underwent surgery or for device occlusion of Fontan fenestration. In these patients, before cardiac catheterization equipment should be ready for temporary or permanent pacemaker implantation because of anteriorly located AV node and fragile conduction system (20) . Presence of clinically important accompanying abnormalities such as ventricular septal defect (VSD), pulmonary stenosis (PS)/atresia can necessitate surgical intervention.…”
Section: Dıscussıonmentioning
confidence: 99%
See 2 more Smart Citations
“…As in our patient group, it is implemented to treat conduit stenosis by percutaneous intervention in patients underwent surgery or for device occlusion of Fontan fenestration. In these patients, before cardiac catheterization equipment should be ready for temporary or permanent pacemaker implantation because of anteriorly located AV node and fragile conduction system (20) . Presence of clinically important accompanying abnormalities such as ventricular septal defect (VSD), pulmonary stenosis (PS)/atresia can necessitate surgical intervention.…”
Section: Dıscussıonmentioning
confidence: 99%
“…The persistence of the morphologic right ventricle as systemic ventricle had resulted in progressive tricuspid regurgitation and ended up with systemic ventricular dysfunction. In terms of long-term results, it was disappointing (1,6,20) . Lundstom et al reported premature deaths in 11 out of 51 cases.…”
Section: Dıscussıonmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these patients had normal left ventricular function with good hemodynamic parameters and all remained asymptomatic at a mean follow-up of 7.6 years (range of 0.5 to 10 years). • The longest surgical follow-up series in CCTGAs was reported by Yeh et al [25], who described the outcome of 127 patients over a 40-year time period • Most recently, Friesen et al [27] reported 7% early mortality among 28 patients with CCTGAs who underwent anatomic repair at Boston Children's Hospital from 1992 to 2002. Of these patients, the DS/AS was performed in 11 patients and DS/R in 17.…”
Section: Double Switch Operationmentioning
confidence: 99%
“…In contrast to most other studies, early follow-up in this study demonstrated equivalent operative mortality for the DS and conventional surgery was associated with a high PM requirement (35% in all patients) for AV block, but long-term follow-up for the DS patients was insufficient to conclude superiority of either approach. Differences in survival may not be evident until a 10-year follow-up has elapsed[25].• Tricuspid valve function was assessed by transthoracic echocardiography performed in 97 patients with AV discordance after palliative procedures, including PA band and Blalock-Taussig shunt, and corrective procedures, including anatomic and physiologic repair. TR increased significantly following Blalock-Taussig shunt, presumably due to volume loading of the systemic RV; TR was significantly reduced following PA banding and anatomic repair, due to reduction of the systemic RV volume.…”
mentioning
confidence: 99%